2023
DOI: 10.1101/2023.01.11.23284254
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Garetosmab, an inhibitor of activin A, reduces heterotopic ossification and flare-ups in adults with fibrodysplasia ossificans progressiva: a randomized, double-blind, placebo-controlled phase 2 trial

Abstract: Background: Fibrodysplasia ossificans progressiva (FOP), an ultra-rare disorder caused by mutations in the gene encoding activin A receptor type 1 (ACVR1), is characterized by painful flare-ups and cumulative heterotopic ossification (HO). Garetosmab, a fully-human monoclonal antibody blocking activin A, prevents HO in FOP mice. Methods: LUMINA-1 (NCT03188666) was a phase 2, multi-center, randomized, double-blind, placebo-controlled study evaluating the safety, tolerability, and effects on HO of intravenous (I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
19
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(21 citation statements)
references
References 24 publications
2
19
0
Order By: Relevance
“…Further details of the clinical trial methods and a description of the study population are reported elsewhere. 11…”
Section: Study Population and Designmentioning
confidence: 99%
See 4 more Smart Citations
“…Further details of the clinical trial methods and a description of the study population are reported elsewhere. 11…”
Section: Study Population and Designmentioning
confidence: 99%
“…In the comparative exposure-response safety analyses, the response variables included the following 5 clinically relevant treatment-emergent adverse events (TEAEs) of special interest: acne, composite abscess, composite skin and soft-tissue infection, epistaxis, and folliculitis. 11 For epistaxis, only moderate or severe cases were considered TEAEs of special interest. The incidence of mild cases of epistaxis was reported previously.…”
Section: Comparative Exposure-response Analysesmentioning
confidence: 99%
See 3 more Smart Citations